2017
DOI: 10.1159/000484454
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin Expression in the Development of Postinfarction Heart Failure

Abstract: Background/Aims: Cholecystokinin (CCK) is expressed in cardiomyocytes and may also play an important role in cardiovascular regulation. Clinical studies have shown that plasma CCK levels are an independent marker of cardiovascular mortality in cardiac disease. However, whether the development of postinfarction heart failure is associated with changes in CCK expression is unknown. Methods: To investigate CCK expression patterns and the association between CCK expression and heart functional parameters, we rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(9 citation statements)
references
References 32 publications
1
7
0
1
Order By: Relevance
“…16) Therefore, we speculate that upregulated CCK may have autocrine or paracrine effects in the pathogenesis of heart failure. 33) In this study, we also observed that ghrelin expression decreased in myocardium as well as the expression of its plasma levels. It is in conflict with the previous studies, in which ghrelin was elevated in cachectic patients with CHF.…”
Section: Discussionsupporting
confidence: 65%
“…16) Therefore, we speculate that upregulated CCK may have autocrine or paracrine effects in the pathogenesis of heart failure. 33) In this study, we also observed that ghrelin expression decreased in myocardium as well as the expression of its plasma levels. It is in conflict with the previous studies, in which ghrelin was elevated in cachectic patients with CHF.…”
Section: Discussionsupporting
confidence: 65%
“…Coupled with the coordinated upregulation of Cacna1b, Cacna1d, Cck, Gabra1, and Gabra2 the pictures is painted less of a neuron and more of an enteroendocrine cell, like a pancreatic β/δ cells or colonic L/I cells [65][66][67] . Canonical satiety peptides (CCK, GLP-1, SST, etc) have a protective effect on peripheral organs in the setting of ischemic damage at the heart 36,[68][69][70][71][72][73] . That the DMV may deliver peptides directly to postganglionic neurons in the periphery adds dimension to the concept of vagal tone as a mediator of health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…BNP'nin ekspresyonu, Western blotlama ve gerçek zamanlı RT-PCR ile kardiyak disfonksiyonun artan zamanı ile anlamlı bir artış sağlamıştır. Dong ve arkadaşları [45] tarafından yapılan çalışmada BNP düzeyleri serumda ELISA metodu ile ölçülmüştür. Kontrol grubuna kıyasla MI gruplarında BNP düzeyleri önemli derecede yüksek bulunmuştur.…”
Section: Sulaiman Ve Arkadaşları [39] Yaptıkları çAlışmaylaunclassified